Coherent dynamics of exciton wave packets in quantum wells and superlattices - Meier, Torsten; Feldmann, J.; Koch, M.; von Plessen, G.; Stolz, W.; Thomas, P.; Göbel, E.O. (Proceedings of the 22nd International Conference on the Physics of Semiconductors ICPS)

Polarization dependence of beating phenomena at the energetically lowest exciton transition in GaAs quantum wells - Meier, Torsten; Mayer, E.J.; Smith, G.O.; Heuckeroth, V.; Kuhl, J.; Bott, K.; Schulze, A.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (Physical Review B)
We report time-resolved degenerate four-wave-mixing experiments on a high-quality single GaAs quantum well. The signals for parallel and cross-polarized exciting pulses show pronounced quantum beats with different frequencies corresponding to the heavy/light-hole splitting and the biexciton binding energy, respectively. Comparison of the experimental data with solutions of the optical Bloch equations for a phenomenological model system shows that these features result from strong contributions of the biexcitonic state. The importance of biexcitons to the nonlinear coherent response of the two-dimension exciton is further confirmed by the frequency dependence of the time-integrated four-wave-mixing signal amplitudes measured for the two polarization geometries.

Ultrafast carrier relaxation and vertical-transport phenomena in semiconductor superlattices: A Monte Carlo analysis - Meier, Torsten; Rossi, F.; Thomas, P.; Koch, S.W.; Selbmann, P.E.; Molinari, E. (Physical Review B)
The ultrafast dynamics of photoexcited carriers in semiconductor superlattices is studied theoretically on the basis of a Monte Carlo solution of the coupled Boltzmann transport equations for electrons and holes. The approach allows a kinetic description of the relevant interaction mechanisms such as intra- miniband and interminiband carrier-phonon scattering processes. The energy relaxation of photoexcited carriers, as well as their vertical transport, is investigated in detail. The effects of the multiminiband nature of the superlattice spectrum on the energy relaxation process are discussed with particular emphasis on the presence of Bloch oscillations induced by an external electric field. The analysis is performed for different superlattice structures and excitation conditions. It shows the dominant role of carrier–polar-optical-phonon interaction in determining the nature of the carrier dynamics in the low-density limit. In particular, the miniband width, compared to the phonon energy, turns out to be a relevant quantity in predicting the existence of Bloch oscillations.

Signatures of Fano-resonances in four-wave mixing experiments - Meier, Torsten; Schulze, A.; Thomas, P.; Vaupel, H.; Maschke, K. (Physical Review B)
Optical transitions into discrete levels coupled to an optically active continuum lead to asymmetrical Fano lines in the linear absorption spectra, reflecting interference between the excitation channels. We investigate the corresponding four-wave-mixing spectra for the nonlinear optical response within a model of noninteracting electrons. Our results show that four-wave-mixing experiments provide a useful tool to identify Fano resonances.

Linear and Non-linear Optical Properties of Semiconductor Superlattices: Excitonic and Field-Induced Effects - Meier, Torsten; Rossi, F.; Je, K.-C; Hader, J.; Thomas, P.; Koch, S.W. (Proceedings of IV International Conference on Optics of Excitons in Confined Systems)
The effective dimensionality of excitons can be drastically changed by applying an alternating electric field. On the basis of a full three-dimensional description of both coherent and incoherent phenomena in anisotropic structures it is found that appropriate applied oscillating fields change the exciton wave function from anisotropic three dimensional to basically two dimensional. This effective-dimension change is caused by dynamic localization which leads to an increase of the exciton binding energy and of the corresponding oscillator strength.

Electric-Field-Induced Exciton Ionization in a GaAs/AlGaAs Superlattice - Meier, Torsten; von Plessen, G.; Koch, M.; Feldmann, J.; Koch, S.W.; Thomas, P.; Göbel, E.O.; Goosen, K.W.; Kuo, J.M.; Kopf, R.F. (Proceedings of IV International Conference on Optics of Excitons in Confined Systems)
We study exciton ionization induced by an axial electric field in a strongly coupled GaAs/Al0.3 Ga0.7 As superlattice at low temperatures. The field-induced ionization times of the heavy-hole 1s exciton in the miniband field regime are determined from transient four-wave-mixing experiments and theoretical model calculations. They are found to lie between the field ionization times of excitons in bulk semiconductors, and in strongly confined quantum well systems.

Quantum beats from biexcitons in narrow quantum wells: polarization and density dependence - Meier, Torsten; Albrecht, T.F.; Schulze, A.; Koch, M.; Bott, K.; Feldmann, J.; Stolz, W.; Kuhl, J.; Mayer, E.J.; Koch, S.W.; Göbel, E.O.; Cundiff, S.T. (Quantum Electronics and Laser Science Conference)
Transient four-wave mixing (TFWM) has been extensively used during the last few years to study exciton dynamics in semiconductors and in semiconductor heterostructures. These studies have provided significant insight into exciton dynamics in both ordered and disordered systems. There are, nevertheless, still certain aspects of the excitonic TFWM response that are not completely understood. In particular, a complete understanding of the polarization and intensity dependences of the signai strength, the decay of the time-integrated signal, and the temporal characteristics of the time-resolved signal has proven elusive. Recent theoretical and experimental work has indicated that exciton-exciton interactions are important.1·2 Such interactions include incoherent processes, such as excitation-induced dephasing, and the formation of biexcitons. Additionally, some of the phenomena result from disorder, making them sample dependent.

Polarization dependence of quantum beats between light-hole and heavy-hole excitons in GaAs quantum wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Bott, K.; Heuckeroth, V.; Thomas, P.; Koch, M.; Hey, R.; Ploog, K. (Quantum Electronics and Laser Science Conference)
The appearance of quantum beats (QBs) between heavy-hole (hh) and light-hole (lh) excitons in GaAs quantum wells (QWs) has been observed in many degenerate-four- wave-mixing (DFWM) experiments with subpicosecond optical pulses. Although the variation of the beat amplitude and phase with polarization of the incident pulses was recognized early on, a consistent theoretical interpretation of exciton coherence for the case of simultaneous excitation of hh and lh excitons is still missing.

Hydrogen interaction with Sb-terminated GaAs and InP (110) surfaces - Santos, Paulo V.; Esser, N.; Groenen, J.; Cardona, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

III-V(110) surface dynamics from anab initiofrozen-phonon approach - Schmidt, Wolf Gero; Bechstedt, F.; Srivastava, G. P. (Physical Review B)

Optical properties of Sb-terminated GaAs and InP (110) surfaces - Santos, Paulo V.; Esser, N.; Cardona, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Se/GaAs(110): energetics and structure - Schmidt, Wolf Gero; Bechstedt, Friedhelm (Surface Science)

Geometrical and electronic structure of the reconstructed diamond (100) surface - Kress, C.; Fiedler, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Quasi-particle band structure of C(111)2 × 1 and C(100)2 × 1 surfaces - Kress, Clemens; Fiedler, Marion; Schmidt, Wolf Gero; Bechstedt, Friedhelm (Surface Science)

Exchange reactions versus adsorption geometries for Se/GaAs(110) - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

III-V(110)/Sb(1 ML): structural and dynamical properties - Schmidt, Wolf Gero; Srivastava, G.P. (Surface Science)

Se/GaAs(110): Atomic and electronic structure - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Influence of scattering on the formation of Wannier-Stark ladders and Bloch oscillations in semiconductor superlattices - Meier, Torsten; von Plessen, G.; Feldmann, J.; Göbel, E.O.; Thomas, P.; Goosen, K.W.; Kuo, J.M.; Kopf, R.F. (Physical Review B)
We study the critical field for the formation of Wannier-Stark ladders and Bloch oscillations in GaAs/AlxGa1−xAs superlattices at low temperatures. From the results of photocurrent and transient four-wave mixing experiments, we conclude that the critical field is higher for superlattices with wide minibands than for superlattices, with narrow minibands. The explanation for this dependence is that intraminiband scattering due to LO-phonon emission is excluded in minibands narrower than the LO-phonon energy.

Coherent electric-field effects in semiconductors - Meier, Torsten; von Plessen, G.; Thomas, P.; Koch, S.W. (Physical Review Letters)
We present a microscopic analysis of coherent effects induced by electric fields in photoexcited semiconductors in the presence of the Coulomb interaction. Both the terahertz emission and four-wave-mixing signals arising from Bloch oscillations in a semiconductor superlattice are computed consistently. It is predicted that Bloch oscillations should be observable also for miniband widths on the order of the exciton binding energy.

Coherent Dynamics of Exciton Wavepackets in Semiconductor Heterostructures - Meier, Torsten; Koch, M.; Feldmann, J.; Göbel, E.O.; Jahnke, F.; Schäfer, W.; Thomas, P.; Koch, S.W.; Nickel, H.; Luttgen, S.; Stolz, W. (Proceedings der 8. International Winterschool on New Developments in Physics)
The coherent dynamics of exciton wavepackets in (GaIn)As/GaAs as well as (GaIn)As/Ga(PAs) multiple quantum well structures is studied by means of transient four-wave mixing (FWM) experiments. The wavepackets are generated by simultaneous excitation of several exciton transitions with laser pulses of about 100 fs duration. The time-integrated FWM signals exhibit a pronounced modulation superimposed on the overall decay which can be attributed to the quantum interference of the different eigenstates. In the time-resolved FWM signals this interference is not present, reflecting the interplay between many-body Coulomb effects and inhomogeneous broadening. This experimental technique is then employed to extract the exciton binding energies in pseudomorphic symmetrically strained (GaIn)As/GaIPAs) with various In contents.